My instructor showed the proof of this result by proving the three axioms of inner product on the given proposed inner product, then using positive definiteness to show the $\ker(A)=\{{\bf 0}\}$. I was wondering if someone could offer an alternative proof that proves both directions of the "if and only if" statement. That is, first assume that $\langle v,w \rangle = (A{\bf v}) \cdot (A{\bf w})$ defines an inner product, why does this mean the $\ker(A) = \{{\bf 0}\}$? Then assume $\ker(A) = \{{\bf 0}\}$, why does this mean $\langle v,w \rangle = (A{\bf v}) \cdot (A{\bf w})$ defines an inner product.


We have that

  1. $$\begin{align}\langle\alpha v1+\beta v_2,w\rangle&=(A(\alpha v1+\beta v_2))\cdot(Aw)\\&=\alpha(Av_1)\cdot(Aw)+\beta(Av_2)\cdot(Aw)\\&=\alpha\langle v_1,w\rangle+\beta\langle v_2,w\rangle\end{align}$$

  2. $$\langle v,w\rangle=(Av)\cdot(Aw)=(Aw)\cdot(Av)=\langle w,v\rangle$$


  1. If $$0=\langle v,v\rangle=(Av)\cdot(Av)$$

we have $Av=0$. Since the kernel is zero we get $v=0$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.